Catholics and American culture : Fulton Sheen, Dorothy Day, and the Notre Dame football team - Massa, Mark Stephen (New York : Crossroad Pub. Co., 1999)
"While in the early years of the century Catholics in America were for the most part distrusted outsiders with respect to the dominant culture, by the 1960s the mainstream of American Catholicism was in many ways "the culture's loudest and most uncritical cheerleader." Mark Massa explores the rich irony in this postwar transition, beginning with the heresy case of Leonard Feeney, examining key figures such as Fulton Sheen, Thomas Merton, and John F.
Kennedy, and concluding with a look at the University of Notre Dame and the transformed status of American Catholic higher education. He shows that the movement toward engagement with - and accommodation to - mainstream American culture was well underway long before Vatican II, with both positive and negative results."--BOOK JACKET.
Introduction: "Oh, the Irony of it All" -- 1. Boundary Maintenance: Leonard Feeney, the Boston Heresy Case, and the Postwar Culture -- 2. Young Man Merton: Thomas Merton and the Postwar "Religious Revival" -- 3. Catholicism as a Cultural System: Joe McCarthy, Clifford Geertz, and the "Conspiracy So Immense" -- 4. "Life is Worth Living": Fulton J. Sheen and the Paradoxes of Catholic "Arrival" -- 5. "The Downward Path": Dorothy Day, Anti-Structure, and the Catholic Worker Movement -- 6. A Catholic for President? JFK, Peter Berger, and the "Secular" Theology of the Houston Speech, 1960 -- 7. "Into Uncertain Life": The First Sunday of Advent 1964 -- 8. "To Be Beautiful, Human, and Christian": The IHM Nuns and the Routinization of Charisma -- 9. Thomism and the T-Formation in 1966: Ethnicity, American Catholic Higher Education, and the Notre Dame Football Team -- Conclusion: Magnalia Christi Americana.
Includes bibliographical references (p. 233-269) and index.
Keywords: Catholic Church -- United States -- History -- 20th century; Catholics -- United States -- History -- 20th century; Christianity and culture -- United States -- History -- 20th century